2020
DOI: 10.3389/fimmu.2020.00692
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific Immunotherapy With Liposome Containing CpG-ODN in Murine Model of Asthma Relies on MyD88 Signaling in Dendritic Cells

Abstract: Changing the immune responses to allergens is the cornerstone of allergen immunotherapy. Allergen-specific immunotherapy that consists of repeated administration of increasing doses of allergen extract is potentially curative. The major inconveniences of allergen-specific immunotherapy include failure to modify immune responses, long-term treatment leading to non-compliance and the potential for developing life-threating anaphylaxis. Here we investigated the effect of a novel liposomal formulation carrying low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Th2 high/eosinophilic asthma can be treated with allergen-specific immunotherapy or symptomatic medication. Allergen-specific immunotherapy is a process that usually increases the circulation of regulatory IL-10-producing cells (Asamoah et al, 2017 ; Alberca-Custodio et al, 2020 ), which could help to curb the pro-inflammatory cytokine storm in COVID-19. Asthma medications, such as corticosteroids and long-acting beta agonists, reduce lung inflammation and provide symptomatic control (Asamoah et al, 2017 ).…”
Section: Asthma Treatment and Covid-19mentioning
confidence: 99%
“…Th2 high/eosinophilic asthma can be treated with allergen-specific immunotherapy or symptomatic medication. Allergen-specific immunotherapy is a process that usually increases the circulation of regulatory IL-10-producing cells (Asamoah et al, 2017 ; Alberca-Custodio et al, 2020 ), which could help to curb the pro-inflammatory cytokine storm in COVID-19. Asthma medications, such as corticosteroids and long-acting beta agonists, reduce lung inflammation and provide symptomatic control (Asamoah et al, 2017 ).…”
Section: Asthma Treatment and Covid-19mentioning
confidence: 99%
“…Additionally, ratio analyses of leucocytes in the BALF indicate macrophage importance. Some studies have shown that their immunoregulatory findings were not always related to the production of IL‐10 by T‐cells, but also by the contribution of antigen‐presenting cells, such as macrophages and dendritic cells 39,58,59 . Therefore, our experimental AIT model could also be influenced by alternatively activated macrophages 60,61 .…”
Section: Discussionmentioning
confidence: 95%
“… 24 On the other hand, several TLR9 agonists have been assessed in combination with an allergen in clinical trials of AIT, demonstrating a strong capacity to induce Th1 response and consequently providing benefit when administered as an adjuvant to AIT. 25 TLR9 activation has been shown to be capable of producing a Th1 response with IFNγ production and IgE synthesis inhibition using modified oligodeoxyribonucleotides containing CpG motifs in a FA animal model 9 and by the co-administration of chenopodium album allergens and CpG in allergic rhinitis patients. 26 , 27 Regarding TLR7 agonists, there are few studies indicating their potential used in AIT, 28 , 29 despite imidazoquinoline compounds (imiquimod and resiquimod), TLR7 agonists have consistently demonstrated a capacity to reverse Th2 responses in favour of an anti-allergic Th1 response and IL-10 production.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of the agonist for TLR4 monophosphoryl-lipid A (MPLA), a less toxic derivative of LPS, together with grass pollen allergens, has been shown to be a booster for AIT, inducing the IFNγ production and reducing the IgE levels in allergic patients. , In addition, the conjugation of MPLA to ovalbumin (OVA) protein has been reported to promote dendritic cell (DC) maturation and induce a Th1 response. , A further small-scale in vitro study in allergic patients has identified MPLA as potentiating allergoid responses in AIT . On the other hand, several TLR9 agonists have been assessed in combination with an allergen in clinical trials of AIT, demonstrating a strong capacity to induce Th1 response and consequently providing benefit when administered as an adjuvant to AIT . TLR9 activation has been shown to be capable of producing a Th1 response with IFNγ production and IgE synthesis inhibition using modified oligodeoxyribonucleotides containing CpG motifs in a FA animal model and by the co-administration of chenopodium album allergens and CpG in allergic rhinitis patients. , Regarding TLR7 agonists, there are few studies indicating their potential used in AIT, , despite imidazoquinoline compounds (imiquimod and resiquimod), TLR7 agonists have consistently demonstrated a capacity to reverse Th2 responses in favour of an anti-allergic Th1 response and IL-10 production. , In addition, one study utilizing nanoparticles with an OVA peptide in the presence/absence of imidazoquinoline compound demonstrated the production of tolerogenic DCs and the induction of Tregs capable of suppressing the response to food challenge .…”
Section: Introductionmentioning
confidence: 99%